Onosma dolichoutum W.T.Wang (Boraginaceae), a new synonym of O. bracteatum Wall. - He, Yi; Hao, Jia-Chen; Liu, Quan-Ru (Phytotaxa, 2018)
Examination of specimens and literatures show that Onosma dolichoutum W.T.Wang, described from Jilong County in southern Xizang, China, matches perfectly the type of O. bracteatum Wall., a common species distributed in subalpine and alpine zones in Western Himalaya. Therefore, we place the former in synonym of the latter. We also designate the lectotype for O. bracteatum. This species is a new record for China.